A Study Of Surgical Management Of Closed Fractures Of Patella - selvan, M.Tamil; S, Prasanth; Thahseen A, Nabeel; kishore.R, Raj; gajapathi, Madhusudanan; sivaprakasam, Keerthi (Journal of Neonatal Surgery, 2025)
Aims and Background: Patella fractures are common in Orthopaedic practice and it comprises about one percent of all traumatic injuries of bone. Inadequate or improper management of the patella fractures will leads to disability. Surgical management of patella fractures were shifted from patellectomy to reconstruction, preservation and restoration of extensor mechanism. The functional outcome studies of closed fractures of patella were few and not studied extensively. The purpose of this study was to analyse the functional outcome of surgical management of closed patella fracture. Methodology: This prospective observational study was carried out on 30 patients. All the adult patients with closed transverse, comminuted, polar patella fractures were included in this study while the open patella fracture and patella fracture associated with femoral condyle, tibial plateau fractures were excluded. All patients underwent various surgical management depends on the fracture pattern and the modified Bostman score was used for assessing the functional outcome. Results: The average age in this study was forty years. Among 30 patients, ten patients were women and twenty patients were men. Majority of fractures (60%) were due to road traffic accident with large percentage of transverse patella fractures (66.6%), and more involvement of left side (73%). The average duration for radiological union was 8 weeks. 90% of patients gave excellent to good results and 10% of patients gave fair results. Conclusions: Our prospective study concluded that closed patella fractures treated by surgical management gave good to excellent functional results in enormous percentage of patients with minimal complications.